Application of nitrogen loaded biochar in purifying agricultural wastewater and as a nitrogen releaser for rice production - Chen, Hongyang; Sun, Yidi; Sun, Yang; Wang, Yanzhi; Li, Yanqi; Wu, Qi; Chi, Daocai (International Journal of Agricultural and Biological Engineering, 2023)
Herein a new approach to the application of agricultural eutrophic wastewater for rice plant cultivation is described. Biochar was used as a medium for the sorption of ammonia from simulated wastewater and subsequently as a nitrogen (N) releaser in the cultivation of rice plants. The main goals of this approach were to isolate ammonia from simulated wastewater and transfer it into rice cultivation, and or explore how exogenous N promoted the growth of rice. The results demonstrate that according to X-ray diffraction phase analysis, most of the properties of biochar were retained before and after loading NH4+-N. Compared with biochar, the crystal peak of AlOOH in N-loaded biochar (NLB) disappeared and the intensity of the crystal peak of CuCaSe2 decreased, which was the important mechanism allowing it to adsorb 30.8% of the N present in simulated low N-concentration agricultural wastewater. The soil N content in NLB treatments was higher than in Non-NLB treatments during the critical tillering and reproductive growth stages. Moreover, the N adsorption-desorption process of NLB matched the N requirements of the rice plant, and thus greatly increased the tiller number by 11.9% and rice yield by 7.5%. These results indicated that the indirect use of ammonia derived from wastewater using biochar as a sorption and releasing medium for rice plant cultivation was promising. This is the first time that biochar was used for possibly indirect reuse of agricultural eutrophic wastewater and enhancement of rice plant growth.Keywords: biochar, ammonia, rice, eutrophic-waterDOI: 10.25165/j.ijabe.20231604.7369Citation: Chen H Y, Sun Y D, Sun Y, Wang Y Z, Li Y Q, Wu Q, et al. Application of nitrogen loaded biochar in purifying agricultural wastewater and as a nitrogen releaser for rice production. Int J Agric & Biol Eng, 2022; 16(4): 257–262.